The Evolution of Vehicle Pneumatic Vibration Isolation: A Systematic Review - Vincent Akolbire Atindana; Xing Xu; Andrews Nanzie Nyedeb; James Kwasi Quaisie; Jacob Kwaku Nkrumah; Samuel Passim Assam (Shock and Vibration)
Whole-body vibration (WBV) is a significant concern for vehicle users as it can negatively impact their health and comfort. As such, effective vibration isolation is critical in vehicle suspension design. The ability of a vehicle suspension to isolate vibrations depends primarily on the suspension design and the type of springs used. One type of spring that has proven advantageous for vibration isolation is the air spring. Air springs can vary frequencies and adjust their stiffness in response to different loading conditions, making them ideal for meeting both suspension load-carrying and occupants’ comfort requirements. Pneumatic (air) suspension has been in use in the automotive industry for several decades and has undergone significant advancements during this period. This paper presents a systematic review of pneumatic suspension since its inception. The review highlights different air spring modeling techniques, types of pneumatic suspension, and control methods. The study also discusses the functional flexibility of pneumatic suspension, its ability to offer a wide range of control options to drivers, and its broad application in almost all ranges of vehicles, including chassis, cabin, and seat suspension systems. In addition, this paper presents a summary of the pros and cons of pneumatic suspension and suggests future research directions. The advantages of pneumatic suspension include effective vibration isolation, improved ride comfort, and the ability to adjust suspension stiffness and ride height. On the other hand, the disadvantages include higher cost and complexity compared to other types of suspension. Overall, the findings of this review demonstrate that pneumatic suspension is a viable solution for vehicle suspension design, particularly in situations where vibration isolation and ride comfort are critical.